The Role Of Entrepreneur Networking In Moderating The Relationship Of Leadership Style To MSME Performance - Lie, Darwin; Sofyan, Sofyan; Rezeki Putri Tanjung, Sri; Chandra, Erbin; Pandapotan Silitonga, Hery (Publisher Cv. Inara, 2023)
This study aims to determine the role of entrepreneurial networking in moderating the relationship of leadership style to the performance of MSMEs in Pematangsiantar City. Literature and field research design with quantitative approach. Research subjects taken in this study are MSME in the city of Pematangsiantar. The research was conducted in eight districts in the city of Pematangsiantar. Data collection techniques using observation, interviews, questionnaires and documentation. The data analysis method used is Partial Least Square (PLS). Data analysis test equipment using Smartpls statistical software. The results obtained were positive and significant between Transformational Leadership with Entrepreneur Networking, Transformational Leadership with MSME performance, and Entrepreneur Networking with MSME performance and positive and no significant between situational leadership with Entrepreneur Networking. Coderation results obtained Entrepreneur Networking is not able to moderate the relationship between situational leadership on MSME performance, and Entrepreneur Networking proved capable of moderating the relationship between transformational leadership on MSME performance.